2020
DOI: 10.1177/0003134820934395
|View full text |Cite
|
Sign up to set email alerts
|

Review of COVID-19 Outcomes in Surgical Patients

Abstract: COVID-19 emerged as a viral pandemic in the year 2019. The practice and scope of surgery and medicine transformed radicially as the virus spread across the world. There is an urgent need to understand the outcomes of COVID-19 infected patients who undergo surgery. We present a comprehensive review of the current literature on the management of surgical patients who develop COVID-19. Findings Poor outcomes were most frequent in general surgery or oncological surgery patients who were older with chronic comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Surgery during the COVID-19 outbreak is challenging to the patient, health care workers, and non-COVID-19 patients [34,35,38,[43][44][45][46] particularly for low and middle-income countries where the limping health care systems were broken with low testing capacity, suboptimal postoperative care, lack of anesthesia machine filters and limited personal protective equipment [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery during the COVID-19 outbreak is challenging to the patient, health care workers, and non-COVID-19 patients [34,35,38,[43][44][45][46] particularly for low and middle-income countries where the limping health care systems were broken with low testing capacity, suboptimal postoperative care, lack of anesthesia machine filters and limited personal protective equipment [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery during the COVID-19 outbreak is challenging to the patient, health care workers, and non-COVID-19 patients [34,35,38,[44][45][46][47] particularly for low and middle-income countries where the limping health care systems were broken with low testing capacity, sub-optimal postoperative care, lack of anesthesia machine lters and limited personal protective equipment [48][49][50][51].…”
mentioning
confidence: 99%
“…Evidence revealed that mortality of patients hospitalized with COVID-19 was very high which is strongly associated with the presence of comorbidities, smoking, and substance use [23,25,34,39,46,[52][53][54].…”
mentioning
confidence: 99%
“…Surgery during the COVID-19 outbreak is too challenging to the patient, health care workers, and non-COVID-19 patients (27,28,31,(37)(38)(39)(40) particularly for low and middle-income countries where the limping health care systems were broken with low testing capacity, sub-optimal postoperative care, lack of anesthesia machine lters and limited personal protective equipment (41)(42)(43)(44).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence revealed that mortality of patients hospitalized with COVID-19 was very high which is strongly associated with the presence of comorbidities, smoking, and substance use (16,18,27,32,39,(45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%